Análise de origem-destino do uso do sistema de transporte coletivo de Curitiba sob o ponto de vista de Regions of Interest - Parcianello, Yussef (2019)
The Public Transportation System (PTS) and its operation management require the processing of large amount of data (bus routes, user data, bus schedules, etc.). Such data provides number of opportunities to identify various facets of user behavior, transport needs and traffic trends. In particular, origin-destination data serve to indicate citizens’ travel patterns and choices, providing insights related to the dynamic of the urban space occupation. Given this scenario, this paper presents a new prototype of origin-destination data visualization developed using only open-source technologies, not requiring any kind of expenses related to the acquisition and /or contracting of software license. The solution is entirely online and does not require the configuration or installation of any type of software or plugin in order to run. Queries can be composed and triggered by the user, and such results can be displayed through different visual representations and aggregated under different levels of detail, always maintaining the spatial and temporal contexts. The tool allows us to understand aspects related to the profile of users of the public transportation, the variation in demand of PTS over a given period, the places where the greatest number of boarding and landings occur, understand the dynamics of urban space occupation, among others. The functionalities offered in the solution were implemented from a list of requirements raised among a group of urban mobility researchers. Results obtained through a usability test indicated that the solution allows lay users to easily perform source-destination analyzes without having to use any programming language and/or data manipulation.